Medical Tourism in Romania. The Case Study of Cardiovascular Rehabilitation in Covasna - Roxana Oana Darabont (Amfiteatru Economic, 2014)
Romania has one of the highest mortality rates in Europe for ischemic heart disease and, especially, for cerebrovascular disease. Taking into account the actual prevalence of cardiovascular diseases, an augmentation of the demand for specialized medical services is expected. As this paper argues, this situation can have an important impact on medical tourism. We analyze original data on the case study of a hospital, specialized in cardiovascular treatment, in the Romanian county of Covasna, which is offering specific balneal procedures, such as CO2 .hydrotherapy, alongside regular rehabilitation programs. The aim of our study is to evaluate the demographic characteristics, and the pathology of the hospitalized patients, as well as the specific rehabilitation procedures. Our findings suggest that the interest of patients, with cardiovascular diseases, for medical tourism can be influenced by accessibility, by some particularities of the location, but also by the holistic nature of the rehabilitation procedures.